2023
DOI: 10.1167/iovs.64.4.21
|View full text |Cite
|
Sign up to set email alerts
|

Capturing the Transition From Intermediate to Neovascular AMD: Longitudinal Inner Retinal Thinning and Factors Associated With Neuronal Loss

Abstract: Purpose To estimate the impact of transition from intermediate to exudative neovascular age-related macular degeneration (AMD) on the inner retina and to assess the relationship of clinical characteristics and optical coherence tomography (OCT) findings with inner retinal changes. Methods A total of 80 participants (80 eyes) with intermediate AMD at baseline who developed neovascular AMD within 3 months were included in the analysis. OCT scans at follow-up visits (after… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…19 Alternatively, a microvascular choroidal failure may be responsible for postreceptoral damage, a theory known as the “ischaemia postreceptoral hypothesis”. 37 Similarly, Woo Lee et al 38 investigated changes occurring to the inner retina in neovascular AMD eyes undergoing intravitreal anti-VEGF therapy and demonstrated a significant progressive thinning of the inner retina in these eyes. They enrolled 52 eyes of patients with exudative AMD who had been treated with at least 3 anti-VEGF injections.…”
Section: Neurodegeneration In Neovascular Amdmentioning
confidence: 99%
“…19 Alternatively, a microvascular choroidal failure may be responsible for postreceptoral damage, a theory known as the “ischaemia postreceptoral hypothesis”. 37 Similarly, Woo Lee et al 38 investigated changes occurring to the inner retina in neovascular AMD eyes undergoing intravitreal anti-VEGF therapy and demonstrated a significant progressive thinning of the inner retina in these eyes. They enrolled 52 eyes of patients with exudative AMD who had been treated with at least 3 anti-VEGF injections.…”
Section: Neurodegeneration In Neovascular Amdmentioning
confidence: 99%
“…The advanced form of AMD is characterized by the development of either macular neovascularization (MNV) or geographic atrophy (GA), which are both responsible for the majority of cases of visual impairment in eyes with AMD [ 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 ]. MNV is characterized by the proliferation of abnormal blood vessels and subsequent leakage due to their immature vascular network.…”
Section: Introductionmentioning
confidence: 99%
“…Neovascularization occurring in nAMD most commonly originates from the choriocapillaris, manifesting as various degrees of exudation in retinal pigment epithelium (RPE) and intraretinal fluid on OCT [ 17 ]. Although AMD is generally considered a disease of the outer retina, much research has shown that both inner and outer retinal layers change during disease progression [ 18 21 ]. However, retinal alterations after intravitreal anti-VEGF therapy for AMD are typically assessed in terms of visual acuity (VA) or central subretinal thickness (CST) in previous studies [ 12 , 22 ], with little emphasis on changes in individual retinal layers or only a single layer such as retinal nerve fiber layer (NFL) or ganglion cell layer (GCL) [ 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%